Sodium glucose transporter 2 (SGLT2) inhibition with empagliflozin improves cardiac diastolic function in a female rodent model of diabetes. Issue 1 (December 2017) - Habibi, Javad; Aroor, Annayya; Sowers, James; Jia, Guanghong; Hayden, Melvin; Garro, Mona; Barron, Brady; Mayoux, Eric; Rector, R.; Whaley-Connell, Adam; DeMarco, Vincent
Abstract Obese and diabetic individuals are at increased risk for impairments in diastolic relaxation and heart failure with preserved ejection fraction. The impairments in diastolic relaxation are especially pronounced in obese and diabetic women and predict future cardiovascular disease (CVD) events in this population. Recent clinical data suggest sodium glucose transporter-2 (SGLT2) inhibition reduces CVD events in diabetic individuals, but the mechanisms of this CVD protection are unknown. To determine whether targeting SGLT2 improves diastolic relaxation, we utilized empagliflozin (EMPA) in female db/db mice. Eleven week old female db/db mice were fed normal mouse chow, with or without EMPA, for 5 weeks. Blood pressure (BP), HbA1c and fasting glucose were significantly increased in untreated db/db mice (DbC) (P < 0.01). EMPA treatment (DbE) improved glycemic indices (P < 0.05), but not BP (P > 0.05). At baseline, DbC and DbE had already established impaired diastolic relaxation as indicated by impaired septal wall motion (>tissue Doppler derived E′/A′ ratio) and increased left ventricular (LV) filling pressure (<E/E′ ratio). Although these abnormalities persisted throughout the study period in DbC, diastolic function improved with EMPA treatment. In DbC, myocardial fibrosis was accompanied by increased expression of profibrotic/prohypertrophic proteins, serum/glucocorticoid regulated kinase 1 (SGK1) and the epithelial sodium channel (ENaC), and the development of these abnormalities were reduced with EMPA. DbC exhibited eccentric LV hypertrophy that was slightly improved by EMPA, indicated by a reduction in cardiomyocyte cross sectional area. In summary, EMPA improved glycemic indices along with diastolic relaxation, as well as SGK1/ENaC profibrosis signaling and associated interstitial fibrosis, all of which occurred in the absence of any changes in BP.